ЎЗБЕКИСТОНЛИК “ҚУРОЛСИЗ АСКАРЛАР”НИНГ УРАЛДАГИ МЕҲНАТ ФАОЛИЯТИДАН - Қурбонов, Х. (SCIENCE and SOCIETY, 2020)
The article describes the creativity, life and the destiny of the Uzbek "unarmed soldiers" who worked a lot in the Urals during the World War II and made a worthy contribution to the Victory.